2020
DOI: 10.1186/s12935-020-01454-x
|View full text |Cite
|
Sign up to set email alerts
|

CircPOSTN/miR-361-5p/TPX2 axis regulates cell growth, apoptosis and aerobic glycolysis in glioma cells

Abstract: Background: Glioma is the most primary central nervous system tumor in adults. The 5 year survival rate for glioma patients remains poor, although treatment strategies had improved in the past few decades. The cumulative studies have shown that circular RNA (circRNA) is associated with glioma process, so the purpose of this study is to clarify the function of circPOSTN in glioma. Methods: The expression levels of circPOSTN, miR-361-5p, and targeting protein for Xenopus kinesin-like protein 2 (TPX2) were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…TPX2, microtubule-associated protein, regulates the dynamics of mitotic spindles, which is indicative of its important role in the cell cycle [26]. In other studies, TPX2 was demonstrated to function as an oncogene, and TPX2 knockdown promoted apoptosis and blocked tumor cell growth [27].…”
Section: Discussionmentioning
confidence: 99%
“…TPX2, microtubule-associated protein, regulates the dynamics of mitotic spindles, which is indicative of its important role in the cell cycle [26]. In other studies, TPX2 was demonstrated to function as an oncogene, and TPX2 knockdown promoted apoptosis and blocked tumor cell growth [27].…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, it can promote the proliferation and migration of human ovarian cancer cells by regulating PLK1 expression [40]. Except for these function, in various cancers can TPX2 also control bladder cancer cell's proliferation and invasion via TPX2-p53-GLIPR1 regulatory circuitry [41], regulate the PI3K/AKT signaling pathway to facilitate hepatocellular carcinoma [42], interactive with miRNA such as miR-485-3p [43], miR-361-5p [44], miR-335-5p [45], miR-216b [46] and so on. Zhou et al have veri ed that TPX2 can activate the epithelial-mesenchymal transition process and promote both the expression and activities of matrix metalloproteinase (MMP)2 and MMP9 in non-small cell lung cancer (NSCLC), which means TPX2 promotes the metastasis and malignant progression of NSCLC and could thus serve as a marker of poor prognosis in NSCLC [47].…”
Section: Discussionmentioning
confidence: 99%
“…Circ-FBXW7 has a tumor suppressor effect in glioma cells by encoding a novel protein and is positively correlated with the overall survival rate ( Yang et al, 2018 ). A recent study found that, apart from regulating cell growth and apoptosis, circ POSTN participated in aerobic glycolysis in glioma via the miR-361-5p/TPX2 axis ( Long et al, 2020 ). Additionally, a recent review reported that most circRNAs function as miRNA sponges in glioma ( Sun et al, 2020 ).…”
Section: Circrnas In Neurological Diseasesmentioning
confidence: 99%